analysis of online crime in social networks - hammouda, saadia; sahraoui, latifa (universty of elouedجامعة الوادي, 2020)
أصبح تحليل الجريمة مجال دراسة بال الأهمية لمساعة فرق تبيق القانون )مثل الشرطة(على حماية المدنيين. بسبب الزيادة السريعة في عدد السكان، زادت معدلات الجريمة بشكل كبير. لهذا، يعتبر التحليل المناسب في الوقت الفعلي خيارا مهما للغاية. يعد تحليل النصوص أداة فعالة يمكن أن تساعد في حل هذه المشكلة و تصنيف الجرائم بكفاءة. يهدف النظام المقترح في هذه المذكرة الى الكشف عن الجرائم الواردة في تعليقات الجزائريين على فيسبوك للتعرف على المدن الخطرة و المدن غير الخطرة في الجزائر. في هذه المذكرة تم استخدام تقنيات التصنيف لكشف الجرائم و تحديد طبيعتها من خلال استخدام خوارزميات التصنيف المختلفة. في الجزء التجريبي، قمنا بتقييم خوارزميات مختتلفة مثل NB, DT, SVM و RF من حيث دقة الكشف في مجال الجريمة. بالإضافة الي ذلك، تم تقييم تقنيات مختلفة لاستخراج الميزات، بما في ذلك وجود الكلمات الموجبة في التعليق HPW، وجود الكلمات السالبة في التعليق HNW، عدد الكلمات الموجبة PWC، عدد الكلمات السالبة NWCوطول التعليق CL. في الأخير، نستنتج أن النتيجة التي حصل عليها مصنف RF هي أفضل نتيجة تم الحصول عليها مقارنة بالمصنفات الأخرى بدقة% 96.1.Crime analysis has become a critical area of study to help law enforcement (such as the police) protect civilians. Due to the rapid increase in population, crime rates have increased dramatically. For this, proper analysis in real time is considered a very important option. Indeed, Text mining is an effective tool that can help solve this problem and categorize efficiently crimes. The proposed system aims to detect crimes in the Facebook comments of Algerians to identify which are the dangerous cities and which are not dangerous cities in Algeria. In this dissertation, classification techniques were used to detect crimes and identify their natures in relation to the different classification algorithms. In the experimentation part, we evaluated different algorithms, such as SVM, DT, NB, and RF, in terms of precision of detection in the crime. In addition, different feature extraction techniques were evaluated, including Has Positives Word (HPW), Has Negative Word (HNW), Positives Word Count (PWC), Negative Word Count (NWC) and Comment Length (CL). Finally, we conclude that result obtained by the RF classifier is the best obtained result compared to other classifiers with an accuracy of 96.1%.
mémouer de fin master infourmatique
Keywords: الجرائم، التعلم الالي، تصنيف، ميزات تقنيات الاستخراج، تعليقات جزائرية، الفيسبوك.; Crimes, Machine learning, Classification, Features extraction techniques, Algerian comments, Facebook.